Education as a Commodity Fetish / A Educação Como Fetiche da Mercadoria - José Bezerra da Silva; Max Silva da Rocha (Universidade Estadual de Alagoas, 2016)
This article analyzes the commercialization process of education under the neoliberal sign and shows the failure of seeking citizenship as the sole teleology able to humanize mankind. Otherwise, the commodity fetishism hides the true social relations, which are conditioned by the class-domination and education stands before the dilemma, or meet the glaring interests of capital or contribute through the implementation of emancipatory educational activities in the mass construction revolutionary. See also the invective of international organizations in collaboration process with peripheral capitalism States in order to fund the basic education and determine the knowledge to be studied. So neoliberalism is seized in schools with a tendency to perpetuate historically